Cluster System as a Strategy for Efficiency in Construction Materials Industry: Sistem Kluster sebagai Strategi Efisiensi dalam Industri Bahan Bangunan - Fayzullayev Jonibek Mambetsaliy O‘g‘li (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Industrial clustering has emerged globally as a strategic approach to enhancing cost efficiency and competitiveness. Specific Background: In Uzbekistan, the construction materials sector is vital to national infrastructure development but remains fragmented, inefficient, and cost-burdened. Knowledge Gap: Despite international successes, limited empirical research exists on the quantifiable benefits of cluster systems within Uzbekistan's construction industry. Aims: This study investigates the potential of clustering to reduce production and logistics costs, enhance technological integration, and improve overall industrial performance. Results: Empirical analysis reveals that cluster-based enterprises achieve a 15% reduction in production costs, 8% lower logistics and energy expenses, and a 50% decrease in waste levels. Labor productivity improves by 22%, technological stoppages are minimized, and export potential doubles. Novelty: Unlike prior studies, this research provides a localized, data-driven assessment linking cluster implementation with measurable efficiency gains, labor inclusion, and innovation adoption. Implications: The findings underscore clustering as a transformative model for Uzbekistan’s industrial policy, supporting sustainable development, small business integration, and regional economic resilience. Highlights: Clustered enterprises reduce production costs by up to 15% and logistics by 8%. Labor productivity increases by 22%, while waste and energy use significantly decline. Export potential, innovation uptake, and small business participation improve dramatically. Keywords: Cluster System, Cost Efficiency, Construction Materials, Innovation, Uzbekistan